GLOBALIZATION DYNAMICS TO FOSTER GROWTH AND DEVELOPMENT WITHIN CIRCULAR ECONOMY: A CASE STUDY OF ALBANIA - Klea Nikolla (Agora International Journal of Economical Sciences (AIJES), 2024)
The linear economy of today's society conflicts with many environmental, social, and economic challenges. As a result, policymakers and researchers prioritize the implementation of the circular economy concept. The European Union supports a smooth transition to a circular economy through the Circular Economy Strategy, the European Green Deal (carbon neutrality by 2050), and the United Nations' Sustainable Development Goals (SDGs). Replacing traditional business models with circular business models necessitates a shift in technology features that incorporate R strategies (refuse, reduce, recycle, etc.). This study looks into how globalization dynamics affect the transition to a circular economy, as well as the implications for growth and development. Albania, as a transitioning economy in Southeast Europe, provides an important backdrop for understanding the problems and opportunities given by globalization when embracing circular economic principles.
Keywords: 330